2015
DOI: 10.1117/1.jbo.20.5.051042
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study on the excystation process in a single unicellular organism amoeba (Acanthamoeba polyphaga)

Abstract: An in vivo Raman spectroscopic study of amoeba (Acanthamoeba polyphaga) is presented. The changes of the spectra during the amoeba cyst activation and excystation are analyzed. The spectra show the changes of the relative intensities of bands corresponding to protein, lipid, and carotenoid components during cyst activation. The presence of carotenoids in the amoeba is observed via characteristic Raman bands. These signals in the Raman spectra are intense in cysts but decrease in intensity with cyst activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The accumulation of carotenoids under stress varies; in Haematococcus pluvialis , the accumulation of carotenoids, that is, astaxanthin, differs based upon the stress conditions such as high light intensity, salinity, acetate addition, and nutrient depletion along with the influence and production of ROS 56 . In the cyst of amoeba, intense Raman bands of carotenoids were observed at 1007, 1156, 1519, 2170, 2315, and 2670 cm −1 ; however, they decrease in the cyst activation 57 . The regulation and migration of carotenoids towards the core give a better confirmation that during germination of seed, carotenoids are upregulated towards the core (radicle inside the seed).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of carotenoids under stress varies; in Haematococcus pluvialis , the accumulation of carotenoids, that is, astaxanthin, differs based upon the stress conditions such as high light intensity, salinity, acetate addition, and nutrient depletion along with the influence and production of ROS 56 . In the cyst of amoeba, intense Raman bands of carotenoids were observed at 1007, 1156, 1519, 2170, 2315, and 2670 cm −1 ; however, they decrease in the cyst activation 57 . The regulation and migration of carotenoids towards the core give a better confirmation that during germination of seed, carotenoids are upregulated towards the core (radicle inside the seed).…”
Section: Resultsmentioning
confidence: 99%
“…56 In the cyst of amoeba, intense Raman bands of carotenoids were observed at 1007, 1156, 1519, 2170, 2315, and 2670 cm À1 ; however, they decrease in the cyst activation. 57 The regulation and migration of carotenoids towards the core give a better confirmation that during germination of seed, carotenoids are upregulated towards the core (radicle inside the seed). From the spectral bands of β-carotene in Figure 6A, we understand that immature mung bean seed stores and contains carotenoids in the cotyledons.…”
Section: β-Carotene As a Signal For Seed Viability And Activationmentioning
confidence: 89%
“…Moreover, the morphological and chemical properties based on RISE confirmed that the carotenoids were not freely secreted but rather integral components on the cell surface. In particular, the significantly enhanced carotenoid Raman signal was associated with enhanced activation and cellular multiplication activities (Lin et al ., 2015). Furthermore, almost all the major peaks of the Raman spectrum for the Pb‐treated cultures (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Показана возможность использования КР спектросопии для исследования эмбрионов млекопитающих и для развития методов преимплантационной диагностики их состояния [8][9][10]. Разрабатываются методы детектирования и исследований патогенных и непатогенных микроорганизмов [11,12]. Использование современных методов статистической обработки и анализа результатов [9,10] с применением методов машинного обучения позволяет облегчить процесс классификации, создание базы данных для практического применения в соответствующих областях.…”
unclassified